The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1103/physrevb.58.13224
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced reconstructions on Cu(211)

Abstract: The chemisorption of oxygen on the vicinal Cu͑211͒ surface and the subsequent reconstructions have been studied by means of He-atom scattering, spot profile analysis-low-energy electron diffraction, scanning tunneling microscopy, and Auger-electron spectroscopy. At temperatures below 250 K oxygen adsorbs without any pronounced ordering whereas at elevated temperatures above 300 K the surface starts to reconstruct and the formation of double steps occurs. Several ordered superstructures have been identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 36 publications
(44 reference statements)
5
50
0
2
Order By: Relevance
“…Note that the symmetry implies the presence of two equivalent domains (denoted by the solid and dashed black lines in Figure 2 c), which are symmetric with respect to the [11 ≈ 0] substrate direction. Additional information about the vertical layer separation (i.e., effective step height) of this phase could be determined by measuring the He-atom reflectivity as a function of the incident wavelength (so called drift measurements [7] ). An analysis of the characteristic interference oscillations, which result from the He-atoms being reflected from the upper and lower terrace of a step, yielded a step height of 3.8(AE 0.2) ä.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the symmetry implies the presence of two equivalent domains (denoted by the solid and dashed black lines in Figure 2 c), which are symmetric with respect to the [11 ≈ 0] substrate direction. Additional information about the vertical layer separation (i.e., effective step height) of this phase could be determined by measuring the He-atom reflectivity as a function of the incident wavelength (so called drift measurements [7] ). An analysis of the characteristic interference oscillations, which result from the He-atoms being reflected from the upper and lower terrace of a step, yielded a step height of 3.8(AE 0.2) ä.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, systems were established which fulfill this requirement, for example, the repair of a thymine ± thymine ± dimer through an excited flavine by Carell and co-workers [7] or the observation of an electron transfer from 2-aminopurine to a next neighbour thymine base by Zewail and co-workers.…”
Section: '-Pivaloylmentioning
confidence: 99%
“…Adsorption on Cu(1 0 0) results in a reconstructed ð ffiffi ffi 2 p  ffiffi ffi 2 p ÞR45°s uperstructure with a similar binding character [24][25][26][27]. Reversible reconstruction with a manifold of superstructures was observed for higher indexed Cu planes like Cu(2 1 1) [28].…”
Section: Introductionmentioning
confidence: 82%
“…In previous related studies, oxygen-induced step-doubling was observed on the Cu(2 1 1) surface along with a transition from monatomic to double-height steps [58,59]. It was reported that oxygen adsorbed without any change in the 2D order at the surface below 250 K, while the surface started to reconstruct and form double-step structures for h O = 0.05-0.10 ML at temperatures above 300 K. The reconstruction started initially at the step edges, and the double step was stable up to 800 K.…”
Section: Ozone (O 3 ) Exposures On the Au(2 1 1) Surface In Uhvmentioning
confidence: 93%